PENGARUH STRUKTUR KEPEMILIKAN SAHAM DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN YANG TELAH TERCATAT DI BURSA EFEK INDONESIA - Kornel Munthe (Jurnal Manajemen., 2014)
The main objective of this research is to know the effect of ownership structure and company size on the performance of manufacturing corporations listed in the Indonesia Stock Exchange. The method of analysis used was linear multiple regression analysis model. This research used secondary data, annual reports of the manufacturing corporations during 2011-2012 with 321 units of corporation as population and 80 units taken as sample by using purposive sampling method. The result of the research indicated that: the managerial ownership, institutional ownership, and company size have positive and significant effects on the performance of the corporation.